TNI MARITIME DIPLOMACY TO MAINTAIN REGIONAL SECURITY STABILITY IN THE FRAMEWORK OF MAINTAINING STATE SOVEREIGNTY - Irwan Shobirin; Surya Wiranto; Aris Sarjito; Priyanto Priyanto; Buddy Suseto; Lukman Yudho Prakoso (Jurnal Cakrawala Ilmiah, 2023)
Indonesian maritime diplomacy is the implementation of foreign policy that is not only related to various maritime aspects at the bilateral, regional and global levels but also uses maritime assets, both civil and military to fulfill Indonesia's national interests in accordance with the provisions of national law and international law. The use of military assets in Indonesian maritime diplomacy is carried out by the Indonesian Navy as one of the main components of national defense which besides having duties in the field of defense and security at sea, also carries out naval diplomacy duties in order to support foreign policy policies set by the government. The objectives of this study are (1) to analyze the cooperative maritime diplomacy of the TNI in order to maintain regional security stability in order to maintain state sovereignty; (2) Analyzing the TNI's persuasive maritime diplomacy in order to maintain regional security stability in order to maintain state sovereignty; (3) Analyze the TNI's coercive maritime diplomacy in order to maintain regional security stability in order to maintain state sovereignty. This study used descriptive qualitative method. The results of this study are (1) The facilities and infrastructure that are owned are still limited, Pusinfomar TNI as the TNI's Balakpus Puspa which is still young is facing a long challenge to become a maritime security data center at the national and international level in supporting the TNI's cooperative maritime diplomacy tasks. Awareness of the importance of maritime information data has not grown nationally so that maritime data has not been properly managed between agencies and Ministries/Agencies and there has not been an exchange of information with regional countries in supporting the TNI's maritime diplomacy tasks through information exchange cooperation with domestic maritime data centers and regional countries Indo-Pacific; (2) The implementation of TNI's persuasive maritime diplomacy in the form of sea security training courses has not been carried out with all regional countries, especially with Vietnam and China, it is necessary to carry out training sessions with the two countries as a form of cooperative maritime diplomacy by using sea power assets in peacetime and building CBM in accordance with their respective national interests as well as to show Indonesia's role as the largest country and founder of ASEAN; (3) The bilateral and multilateral Patkor has not yet been fully implemented as a form of coercive maritime diplomacy between the TNI and neighboring countries in the face of the vastness of Indonesia's sea boundaries and the strategic bangling situation in the Indo-Pacific region, especially in the SCS region where ZEEI LNU borders with ZEE Vietnam and Malaysia